Tensiometric investigation of the interaction and phase separation in a polymer mixture–ionic surfactant ternary system - JAROSLAV M. KATONA; VERICA J. SOVILJ; LIDIJA B. PETROVIĆ; NENAD Z. MUCIĆ (Journal of the Serbian Chemical Society, 2010)
The interaction and phase separation in a ternary mixture composed of hydroxypropyl methyl cellulose (HPMC), sodium carboxymethyl cellulose (NaCMC), and sodium dodecylsulfate (SDS) were investigated by tensiometry. Surface tension measurements of binary mixtures (0.7 % HPMC and 0.00–2.00 % SDS) and of ternary mixtures (0.7 % HPMC, 0.3 % NaCMC, and 0.00–2.00 % SDS) were performed. The measurements indicated interaction between HPMC and SDS, which resulted in HPMC–SDS complex formation. The critical association concentration, CAC, and polymer saturation point, PSP, were determined. Phase separation of ternary HPMC/SDS/NaCMC mixtures occurs at SDS concentration > CAC, i.e., when the HPMC–SDS complex is formed. The volume of the coacervate increases with increasing SDS concentration, and at SDS concentrations > 1.00 %, the coacervate vanishes. The surface tensions (s) of ternary HPMC/SDS/NaCMC mixtures in the pre-coacervation region and at the onset of the coacervation region are similar to the σ of the corresponding binary HPMC–SDS mixtures, while in the coacervation and post coacervation region, they are close to the s of the corresponding SDS solutions